Ophthalmic Manifestations and Histopathology of Xeroderma Pigmentosum: Two Clinicopathological Cases and a Review of the Literature - Ramkumar, Hema L. (2011)
Xeroderma pigmentosum is a rare, autosomal recessive disease caused by a defect in DNA repair. Patients with xeroderma pigmentosum often have cutaneous and ocular sun sensitivity, freckle-like skin pigmentation, multiple skin and eye cancers, and, in some patients, progressive neurodegeneration. Xeroderma pigmentosum predominantly affects the UV exposed ocular surface, resulting in eyelid atrophy and cancers, corneal dryness, exposure keratopathy, and conjunctival tumors. We report the clinical history and ocular pathology of two Caucasian women who had xeroderma pigmentosum with neurological degeneration: Case 1, who died at age 44 and Case 2, who died at age 45. Case 1 with mutations in the XPA gene, had more than 180 basal cell carcinomas of her skin and eyelids and died from complications of neurodegeneration. Case 2, with mutations in the XPD gene, was sun protected and had 3 skin cancers. She died from complications of neurodegeneration and pneumonia. Both patients had bilateral pinguecula, corneal pannus and exposure keratopathy. Case 1 had bilateral optic atrophy, while Case 2 had bilateral peripheral retinal pigmentary degeneration. Both patients developed retinal gliosis. The ophthalmic manifestations and pathology of xeroderma pigmentosum are discussed and reviewed with respect to this report and other cases in the literature. These cases illustrate the role of DNA repair in protection of the eyes from UV damage and neurodegeneration of the retina.